Intraductal dissemination of ampullary carcinoma after pancreatoduodenectomy - Koichi Mohri; Kazuhiro Hiramatsu; Yoshihisa Shibata; Motoi Yoshihara; Taro Aoba; Atsuki Arimoto; Akira Ito; Takehito Kato (Surgical Case Reports)
Abstract Background Clinical evidence of intraductal dissemination through the pancreatic duct has been rare. We herein describe a case of ampullary carcinoma that disseminated in the remnant pancreas through the pancreatic duct. Case presentation A 68-year-old woman underwent SSPPD for ampullary carcinoma. The tumor was diagnosed as adenocarcinoma without lymph node metastasis (T2N0M0, stage IB). Computed tomography (CT) performed 3 years later revealed a 14-mm tumor near the site of the pancreaticojejunal anastomosis. Endoscopic ultrasound-guided fine needle aspiration showed adenocarcinoma that was morphologically similar to the specimen from the first surgery. We diagnosed recurrence of ampullary carcinoma in the remnant pancreas. A total remnant pancreatectomy was performed. We found a white solid tumor at the 20-mm distal side of pancreaticojejunal anastomosis. The tumor was morphologically similar and immunostaining showed a pattern identical to that of the original tumor, suggesting that the two tumors were of the same origin. Conclusion The recurrent lesion was most likely the result of tumor cells leaving the tumor and implanting in the remnant pancreatic duct epithelium. Intraductal dissemination of adenocarcinoma is thought to be a cause of remnant recurrence after SSPPD in cases of obstruction of the pancreatic duct or an iatrogenic procedure.